Pyogenic liver abscesses Analysis of the study and treatment.: About seven observations - Czarnevicz, Daniel; Radio, Alvaro; Secondo, Gerardo; Kaitazzof, Pedro; Retich, Gizalle; Howard, Graciela; Torterolo, Edgardo (Cirugía del Uruguay, 1994)
This paper analyses the treatment of seven hepatic pyogenic abscesses at Clínica Quirúrgica 2 (Surgical Clinic 2) directed by Prof. Dr. Ce/so Silva during 6 months. Five of them were treated by means of percutanous drainage guided by echography; this procedure is of easy realization, /ow morbility and satisfactory therapeutica/ results when indicated.